Tipologi Tindak Pidana Korupsi di Sektor Pertanahan dan Implikasinya pada Pemanfaatan Tanah Negara di Indonesia - Arfah, Muhammad; Amriyanto, Amriyanto (Faculty of Law, Khairun University, 2018)
Land that is directly controlled by the state can be granted ownership rights, business use rights, building rights and use rights, both to individuals and to legal entities. With regard to the granting of these rights, these lands can also be encumbered with mortgage rights. Indications of criminal acts of corruption in granting such land rights may occur. Execution of state booty in corruption cases has the potential to harm other parties, if the state booty is burdened with mortgages.